2021
DOI: 10.1302/0301-620x.103b7.bjj-2020-2064.r1
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of the largest possible metal head increase the wear of vitamin E-doped cross-linked polyethylene? Two-year results from a randomized controlled trial

Abstract: Aims We aimed to investigate if the use of the largest possible cobalt-chromium head articulating with polyethylene acetabular inserts would increase the in vivo wear rate in total hip arthroplasty. Methods In a single-blinded randomized controlled trial, 96 patients (43 females), at a median age of 63 years (interquartile range (IQR) 57 to 69), were allocated to receive either the largest possible modular femoral head (36 mm to 44 mm) in the thinnest possible insert or a standard 32 mm head. All patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…HXLPE liners with vitamin E do not show statistically significant lower wear rates, even when combined with the largest possible head. 30,31 Together, all studies reporting excellent wear rates with thin liners contradict an earlier in vitro report by Johnson et al, 10 which found higher wear rates in thinner HXLPE liners compared to thicker HXLPE liners.…”
Section: Discussionmentioning
confidence: 85%
“…HXLPE liners with vitamin E do not show statistically significant lower wear rates, even when combined with the largest possible head. 30,31 Together, all studies reporting excellent wear rates with thin liners contradict an earlier in vitro report by Johnson et al, 10 which found higher wear rates in thinner HXLPE liners compared to thicker HXLPE liners.…”
Section: Discussionmentioning
confidence: 85%
“…They reported that the mid‐term wear, cup migration, and clinical outcomes did not differ between the different head size groups, and their annual linear wear rates ranging from 0.023 to 0.028 mm/year were well below 0.1 mm/year of the wear threshold to increase the frequency of osteolysis 38 . In another study, Tsikandylakis et al 39 reported on 88 hips treated either with the largest possible (36–44 mm) metal head in the thinnest possible (4.3–5.3 mm) Vit‐E diffused XLPE liner or a standard diameter metal head (32 mm) in 6.7–11.3 mm‐thick Vit‐E diffused XLPE liner. They showed that the use of the largest possible heads did not significantly increase wear compared with 32 mm heads at 2 years although there was a tendency toward higher values of volumetric wear in the largest possible heads.…”
Section: Discussionmentioning
confidence: 97%
“…This finding aligns with previous studies that demonstrated that total head penetration and wear rates are independent from femoral head size. [27][28][29] No patients experienced aseptic loosening, and only one underwent revision due to dislocation two days after surgery. Given that the THA lifespan is usually 20 years, 2,14 the sample size was small, and the wear rate was low, other revisions would have been unlikely.…”
Section: Discussionmentioning
confidence: 99%